Лучшие помощники
- Megamozg 2205 б
- Matalya1 1800 б
- DevAdmin 1720 б
- arkasha_bortnikov 895 б
- Dwayne_Johnson 860 б
2 апреля 2023 13:33
1033
2sinxcosx - 2sinx - cosx + 1 = 0` после лета ваще не варит понимаю что с группировкой
1
ответ
2sinxcosx - 2sinx - cosx + 1 = 0
2sinx(cosx-1) - (cosx-1) = 0
(cosx - 1)(2sinx-1) = 0
cosx = 1 sinx = 1/2
x = 2Пk x = (-1)^n *П/6 + Пn, k,n: Z
2sinx(cosx-1) - (cosx-1) = 0
(cosx - 1)(2sinx-1) = 0
cosx = 1 sinx = 1/2
x = 2Пk x = (-1)^n *П/6 + Пn, k,n: Z
0
·
Хороший ответ
4 апреля 2023 13:33
Остались вопросы?